Sennsory Textural Attributes Of A Fruit-Filled Microwaveable Waffle Product - Frey, Sherry A. Stam (Kansas State University, 1998)
Lowfat, frozen, microwaveable, on-the-go, fruit-filled Belgian waffles (Waf-Fills) were evaluated by trained panelists for crispness, toughness, surface roughness, scorching, color evenness, and color lightness. Five treatments of microwave powers and heating times were compared. Significant differences were observed for degree of scorching, surface roughness, and crispness with attributes more affected by time than power. Overall appearance, flavor, texture, and product acceptability (n = 51) of strawberry flavored breakfast products were significantly higher for Toaster Strudels than Waf-Fills, Eggos, and Pop-Tarts. Few consumers perceived waffles as snacks. A majority indicated preference for lowfat products, but only a third changed their overall product preference on that basis.